(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article describes the connection between Mapuche rural cultural spaces and those re-created in urban areas and their connection with the construction of ethnic identity in urban Mapuche adolescents. This is a qualitative and descriptive study and the data is analyzed through the approach of discourse analysis of discursive psychology (Edwards y Potter, 1998, 2000) and considers the notion of place identity by Proshansky (1978). The research population were thirty Mapuche adolescents living in Santiago and thirty living in Temuco. These adolescents were interviewed by a Mapuche interviewer. The findings reveal that the re-created urban cultural spaces fulfill a mediating role in the change from original places to new ones (Proshansky et al., 1983), which allows these adolescents to reinforce their ethnic identity construction.